Climate Change Impacts on Livestock - Thornton, Philip K.; Boone, Randall B.; Ramírez Villegas, Julián Armando (2015)
This Working Paper summarizes projected climate change impacts on livestock across Africa, using a combination of literature review and some new results on the projected impacts of climate change on the rangelands of Africa. Findings show that there are many options that can help livestock keepers adapt, but there appear to be no options that are widely applicable which do not have constraints to their adoption. An enabling technical and policy environment will thus be needed to ensure livestock keepers can adapt to climate change and enhance their livelihoods and food security.